Diseño de filtros paso-banda mediante cavidades resonantes en tecnología SIW multicapa - De-Oliva-Rubio, José; López Berrocal, Benito; Molina-Fernández, Íñigo (My University, 2017)
This document discusses the design of coupled resonators band-pass microwave filters. The resonators are implemented as substrate integrated waveguide (SIW) rectangular cavities, which are piled vertically in a multilayer board. The coupling elements are composed by slots opened in the horizontal metallization layers separating the resonators. Each coupling element introduce simultaneous cross-couplings among several resonators. The principal contribution of this work consists on the proposal of a highly flexible design technique for the implementation of any arbitrary coupling matrix with the formerly described physical structure. The technique relies on the hypothesis that the overall effect of several coupling elements is approximately equal to the lineal combination of the effects of the individual elements. The versatility of the proposal has lead to the design and implementation of a variety of filters with very different coupling matrix topologies, sharing the same physical structure and the same type of coupling elements. Besides, given the order of the filter, its size remains the same despite the topology of its coupling matrix. In this document one of these designs is discussed: a box-section filter with asymmetric response including one transmission zero.
Keywords: Radio; Filtro SIW; Resonadores acoplados; Cavidades resonantes